Réponses

2014-04-14T20:17:59+02:00
Bonsoir

3/5(x -5/7) = 3x /10
3x /5 - 5/7 = 3x/ 10
on met tout sous 70
42x - 50 = 21x
42x - 21x = 50
21x = 50
x = 50/21

1/3x = -2(1/3x -2)
1/3x = -2 ( x/3 - 6/3)
x = -2(x -6)
x = -2x +12
x +2x = 12
3x =12
x = 4

(2x+3)(5-2x) + (5-2x) ( 9-x ) = 0
(5-2x)(2x+3 + 9-x) = 0
(5-2x)(x +12) = 0
soit 5 - 2x = 0
-2x = -5 et x = 5/2
soit x +12 = 0 et x = -12

(x-7)² - (3 -5x)(x-7) = 0
(x-7)(x-7 - 3 +5x ) = 0
(x-7) ( 6x -10) =0
soit x -7 = 0 et x = 7
soit 6x -10 = 0
6x = 10
x = 6/10 = 3/5